The Relationship Between The Bystander Effect and Prososial Behavior in Students Of The Faculty Of Psychology And Educational Sciences At University: Hubungan Antara Bystander Effect dengan Perilaku Prososial pada Mahasiswa Fakultas Psikologi dan Ilmu Pendidikan di Universitas - Istanti Nur Fadilah; Eko Hardi Ansyah (Academia Open, 2022)
The purpose of this study was to determine the relationship between the bystander effect and prosocial behavior in students of the Faculty of Psychology and Educational Sciences at Muhammadiyah University of Sidoarjo. The population in this study were students of the Faculty of Psychology and Educational Sciences at the Muhammadiyah University of Sidoarjo, totaling 2,145 students and the sample of this study was 337 students who were taken using incidental sampling technique. The data collection technique used a psychological scale with a Likert scale model. The data analysis technique used is the product moment correlation technique assisted by SPSS 16.0 for windows. The results of data analysis show that there is a significant positive relationship between the bystander effect and prosocial behavior in students of the Faculty of Psychology and Educational Sciences at Muhammadiyah University of Sidoarjo. Highlights: The study examines the relationship between bystander effect and prosocial behavior in students of the Faculty of Psychology and Educational Sciences. The population consists of 2,145 students, with a sample of 337 students selected using incidental sampling technique. Data analysis using the product moment correlation technique reveals a significant positive relationship between the bystander effect and prosocial behavior in the studied student population. Keywords: Bystander effect, Prosocial behavior, Students, Muhammadiyah University of Sidoarjo, Correlation analysis